THE EFFECT OF GAMMA IRRADIATION TO THE PHENOTYPIC OF TWO AGLONEMA VARIETIES - Arya Widura Ritonga; Dewi Sukma (Universitas Sembilanbelas November Kolaka, 2017)
Increased phenotypic diversity is needed to increase the economic value of Aglaonema. However, information on increasing phenotypic diversity of Aglaonema using gamma-ray irradiation has not been widely known. This study aimed to investigate the effect of gamma ray irradiation treatment to the performances of two varieties of Aglaonema. This research was arranged factorially using randomized group design (RKLT) of two factors consisting of 8 combinations of treatments that are 4 level of irradiation dose and 2 Aglaonema varieties. The results showed that the induction of gamma ray irradiation decreased the % viable of the plants, the number of leaves, leaf length, leaf width, and the % green color as well as increased the % blue on the leaves of Aglaonema Butterfly and Aglaonema Siam Aurora. The interaction between dose of irradiation and aglaonema varieties was obtained in the % red of leaf color. Both of Aglaonema varieties had a high radiosensitivity with LD50 values ranged of 16.70 - 17.14 Gy